Development planning in East Africa - Clark, Paul G. (Nairobi : Published for the East African Institute of Social Research [by the] East African Pub. House, 1965)
The author of this book attempts to consider the development process of East Africa as a comprehensive whole, using statistical information wherever possible and trying to deal concretely with policy issues.
Includes bibliographical footnotes.
hza 29/01/2019
Loans
Keywords: Economic development; Economic planning; Africa, East